Ortho‐Fluoroazobenzenes: Visible Light Switches with Very Long‐Lived Z Isomers. Issue 50 (28th October 2014) - Knie, Christopher; Utecht, Manuel; Zhao, Fangli; Kulla, Hannes; Kovalenko, Sergey; Brouwer, Albert M.; Saalfrank, Peter; Hecht, Stefan; Bléger, David
Abstract Improving the photochemical properties of molecular photoswitches is crucial for the development of light‐responsive systems in materials and life sciences. ortho‐Fluoroazobenzenes are a new class of rationally designed photochromic azo compounds with optimized properties, such as the ability to isomerize with visible light only, high photoconversions, and unprecedented robust bistable character. Introducing σ‐electron‐withdrawing F atoms ortho to the NN unit leads to both an effective separation of the n→π* bands of the E and Z isomers, thus offering the possibility of using these two transitions for selectively inducing E/Z isomerizations, and greatly enhanced thermal stability of the Z isomers. Additional para‐electron‐withdrawing groups (EWGs) work in concert with ortho‐F atoms, giving rise to enhanced separation of the n→π* transitions. A comprehensive study of the effect of substitution on the key photochemical properties of ortho‐fluoroazobenzenes is reported herein. In particular, the position, number, and nature of the EWGs have been varied, and the visible light photoconversions, quantum yields of isomerization, and thermal stabilities have been measured and rationalized by DFT calculations.